UMP journal tops automotive engineering ranking again - UMP, PNC (Pejabat Naib Canselor, 2016)
A journal published by Universiti Malaysia Pahang (UMP) Press has been recognized as the best in Asia three years in a row, registering the highest indices for production and publication of scientific articles in the fields of automotive and mechanical engineering.